2018
DOI: 10.1177/0961203318770018
|View full text |Cite
|
Sign up to set email alerts
|

Lupus myocarditis: a single center experience and a comparative analysis of observational cohort studies

Abstract: Background Lupus myocarditis (LM) is reported in 3-9% of patients with systemic lupus erythematosus (SLE) but limited evidence exists regarding optimal treatment and prognosis. This study aims to describe LM in a defined lupus cohort as compared with the existing literature. Patients and methods Patients with LM were identified from the University of Toronto Lupus Clinic database. Diagnosis was based on clinical manifestations and electrocardiographic, imaging, and biochemical criteria. Demographic, clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 26 publications
0
24
1
5
Order By: Relevance
“…Previous reports showed that prevalence of lupus myocarditis is 5–10% of patients [ 3 , 4 ], and mortality may be as high as 10.3% according to a large case series from Paris [ 6 ]. Although other studies report that concomitant lupus activity in various organ occurs in 97% of the patients with lupus myocarditis [ 7 ], our report provides a rare evidence that lupus myocarditis may be a sole manifestation. Clearly, given the rarity of myocardial involvement, diagnosis is elusive.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous reports showed that prevalence of lupus myocarditis is 5–10% of patients [ 3 , 4 ], and mortality may be as high as 10.3% according to a large case series from Paris [ 6 ]. Although other studies report that concomitant lupus activity in various organ occurs in 97% of the patients with lupus myocarditis [ 7 ], our report provides a rare evidence that lupus myocarditis may be a sole manifestation. Clearly, given the rarity of myocardial involvement, diagnosis is elusive.…”
Section: Discussioncontrasting
confidence: 52%
“…The importance of targeting inflammatory mediators of myocardial damage to improve patient's outcome was also emphasized in three monocentric cohorts of patients who developed myocarditis in the context of CTDs. In this studies MMF was the first-line immunosuppressive therapy in 4 out of 12 patients with anti-synthetase syndrome [39], in 6 out of 30 patients with SLE [41], and in 3 patients with myocarditis in the context of anti-Ku positive SSc [18]. However, follow-up data were not reported in these studies and firm conclusions cannot be drawn.…”
Section: Mycophenolate Mophetilmentioning
confidence: 83%
“…Clinical and experimental evidence to support the use of B-cell depletion therapy with anti-CD20 monoclonal antibody rituximab (RTX) is poor. To date, only few observational studies and case reports described the efficacy of rituximab in VNM related to connective tissue diseases, mainly SLE [40,41,48].…”
Section: Rituximabmentioning
confidence: 99%
“…In the differential considerations of a patient with decompensated heart failure without typical cardiovascular risk factors, we find that, despite several cases being reported, heart failure as the initial manifestation of SLE remains exceedingly rare in the literature, as was observed in a large lupus cohort in Toronto over a period of more than 40 years. Acute lupus myocarditis as the presenting symptom of SLE remains a rare entity, with only 0.37% of patients presenting as such [23]. Due to lack of evidence-based consensus or a comprehensive review of the same, heart failure due to SLE continues to be an underrecognized phenomenon, thereby significantly delaying diagnosis and initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%